Pengaruh Pendidikan Agama Islam terhadap Perkembangan Ahlak Anak di Kampung Cibalung - Tanzil Khoerul Akbar; Koko Khoerudin (CV. Green Publisher Indonesia, 2026)
This research is motivated by the low level of children’s moral behavior, which is indicated by a gap between religious knowledge and the practice of Islamic values in daily life. Islamic religious education still tends to emphasize memorization rather than value internalization and moral development. This study aims to examine the effect of Islamic religious education on the moral development of children in Kampung Cibalung, Bogor. The research employed a quantitative approach using a survey method. The population of the study consisted of parents who have school-aged children in Kampung Cibalung, Bogor, with a sample of 40 respondents selected through probability sampling techniques. Data were collected through a closed-ended questionnaire using a four-point Likert scale and distributed online. The data were analyzed using descriptive statistics and simple regression analysis. The results indicate that Islamic religious education has a significant effect on children’s moral development, with a significance value of 0.000 and a coefficient of determination of 55.4%. These findings demonstrate that Islamic religious education has a strong contribution to shaping children’s morals, particularly when it focuses not only on memorization but also on understanding and the application of Islamic values in daily life